Implementation of Culturally Responsive Teaching (CRT) Approach in Improving Critical Reasoning Ability and Collaboration of Grade IV Elementary School in Science Subject in Pagedongan District - Nurul Farida Istiqomah; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
This research aims to determine the implementation of culturally responsive teaching (CRT) approach on critical thinking and collaboration for class IV elementary school for the IPAS learning in Kecamatan Pagedongan. This type of research is quasi-experimental research with The pretest-posttest control group design. Data on critical thinking and collaboration was collected using an assessment instrument in the form of a questionnaire. Data was analyzed using analysis assisted by SPSS 23 for Windows. The results of the research show that: First, there is a significant influence of culturally responsive teaching (CRT) approach on the critical thinking IPAS of class IV students at elementary school Kecamatan Pagedongan. Second, there is a significant influence of culturally responsive teaching (CRT) approach on the collaboration IPAS of class IV students at elementary school Kecamatan Pagedongan. And third, there is a significant influence of culturally responsive teaching (CRT) approach on the critical thinking and collaboration IPAS of class IV students at elementary school Kecamatan Pagedongan.